El derecho a recurrir de la parte actora dentro del procedimiento ejecutivo a la luz de la sentencia 350-19-ep de la Corte Constitucional del Ecuador - Puerres Villarreal, Adrián Santiago (2024)
The right to appeal is a human right recognized in International Law, in Ecuadorian law it is established as a basic guarantee of the right to due process, this research was developed based on the analysis of the sentence No. 350-19-EP of the Constitutional Court of Ecuador, issued on the grounds of violation of the right to appeal of the plaintiff due to the provision of Article 352 of COGEP concerning the executive procedures. The general objective of the research is to analyze the right to appeal through the critical and hermeneutic study of sentence No. 350-19-EP of the Constitutional Court in order to identify if in the Civil Judicial Unit of Ibarra there are cases from the year 2023 in which the plaintiff has filed an appeal of the first instance sentence dictated in application of art. 352 COGEP. The research was carried out with a mixed approach, and with a level of depth both descriptive and exploratory, in relation to the fact that there are no recent works with similar subject matter and it was examined by means of deductive, analytical, normative and hermeneutic methods. It is inferred that the Constitutional Court establishes the violation of the right to appeal by the judge of first instance of the Civil Judicial Unit of the Metropolitan District of Quito, that the provision of article 352 of the COGEP contains two assumptions that must be met imperatively and continues to disqualify the filing of an appeal against the judge's decision.